KINERJA BADAN KEPEGAWAIAN DAERAH DALAM PROSES PEREKRUTAN APARATUR NEGERI SIPIL DI KABUPATEN WAROPEN PROVINSI PAPUA - WATOPA, LAZARUS; RORONG, ARIE JUNUS; TAMPI, GUSTAF BUDI (Sam Ratulangi University, 2018)
The purpose of this research is to know the performance of Regional Personnel Agency In Civil ApparatusRecruitment Process. This research uses qualitative approach method. which was proposed by Gibson thatis effectiveness, efficiency, accountability and justice. The research informant is the Head of BK Service (1Person): Secretary BKD (1 Person); Employee BKD (3 Persons) Applicants CPNS (5 Persons). Data wascollected using interview guidelines, while the analytical technique used was interactive model analysisfrom. Based on the results of data analysis, it is concluded that the effectiveness of the administration of theWaropen Regency administration, especially the Regional Personnel Agency of Waropen Regency, is seenfrom the indicators of effectiveness, efficiency, accountability and justice is not good. Based on the resultsof research can be recommended suggestions: 1. Waropen County Government, especially the RegionalPersonnel Agency Waropen Regency. Expected to further improve its performance; 2. It is necessary tomaintain and enhance the integrity and integrity of resources in the scope of the BKD, especially the attitudeand consistency of the responsibilities in order for each realization of the work program to be resolved asexpected; 3.The form of responsibility is further enhanced so that the bias gives the public trust andmaintains the authority of the government at the community level; 4. Maintaining existing professionalismso that recruitment of candidates for civil servants is not indicatedKeywords: Performance, Governmental Apparatus